Religion and the State A Comparative Sociology - Barbalet, Jack; Possamai, Adam; S. Turner, Bryan (Key Issues in Modern Sociology, 2011)
With a clear statement of the theoretical issues in the debates about secularization and post-secularism, 'Religion and the State: A Comparative Sociology' considers a number of major case studies - from China, Europe, Singapore and South Asia - in order to understand the rise of public religions in the modern state. By distinguishing between political secularization - the separation of state and religion - and social secularization - the transformation of the everyday practice of religion - this volume offers an integrating framework within which to analyze these different societies.